High-capacity core-shell structure ultrahigh nickel positive electrode material and preparation method thereof

By adopting core-shell structure and cladding technology, the cycle stability and safety performance of the positive electrode material of ultra-high nickel lithium-ion battery is improved, and the shortcomings of existing materials in cycle stability, thermal stability and safety performance are solved, so as to achieve High capacity and long life battery performance.

CN119481008APending Publication Date: 2025-02-18NANTONG RESHINE NEW MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411673719.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing ultra-high nickel lithium-ion battery cathode materials have shortcomings in cycle stability, thermal stability and safety performance, which limits their large-scale commercial applications.

Method used

The high-nickel positive electrode material preparation method adopts a core-shell structure. Through a one-mix and multi-stage sintering process, Al2O3, Nb2O5 and lithium hydroxide are combined to form an active LiAlO2 and LiNbO3 coating layer to improve the ion permeability of the material.

Benefits of technology

The cathode material with high capacity and long cycle life has achieved a specific capacity of 224.8mAh/g for the first discharge, and the capacity retention rate of 100 cycles of 45℃ high-temperature cycle reaches 90%, which significantly improves the circulation and safety performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481008A_ABST
    Figure CN119481008A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium battery positive electrode material production processes, and particularly discloses a preparation method of a high-capacity core-shell structure ultrahigh nickel positive electrode material, which comprises the following steps: S1) primary mixing: uniformly mixing a high-nickel multi-element precursor NixCoyMnz (OH) 2 with a concentration gradient structure, lithium hydroxide powder and a compound A containing one or more elements of Al, Mg, Zr, Ti, W, V, Mo, B and Y; s2) primary sintering: adopting a multi-stage sintering process; and S3) washing: carrying out a water washing process by adopting vertical filter pressing so as to reduce residual alkali on the surface of the high-nickel material. S4), secondary mixing and coating; and S5), secondary sintering. According to the invention, Al2O3 and Nb2O5 are adopted for co-coating, and an active substance coating layer is formed on the surface of the NCM material, so that the stability of the material and the ion permeability of the coating layer are improved. And the core-shell precursor is adopted, and the high-capacity excellent-cycle core-shell structure positive electrode material is synthesized through the process route of primary material mixing, sintering, coarse crushing, washing, coating, sintering and iron sieving.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of production technology of lithium ion battery positive electrode materials, and in particular to a high-capacity core-shell structure ultra-high nickel positive electrode material and a preparation method thereof. Background Art

[0002] In recent years, electric vehicles from companies such as Tesla and BYD have swept across China, continuously injecting vitality into the battery industry. Compared with lithium cobalt oxide positive electrode materials, high-nickel positive electrode materials for lithium-ion batteries (nickel content exceeds 60%) have the advantages of high energy density and low price. In an era of pursuing cost-effectiveness, lightweight and high mileage, it can provide higher specific capacity and lower price, and is one of the most promising battery positive electrode materials.

[0003] As the nickel content in the ternary material increases, its specific capacity gradually increases, but at the same time the material's cycle stability, thermal stability and safety performance are significantly reduced, which greatly limits the large-scale commercial application of ultra-high nickel ternary materials. Both the core and the shell of the core-shell material are electrochemically active, and it is expected to take into account both long cycle life and high specific capacity. However, studies have found that due to the large differences in composition between the core and the shell, obvious cracks are easily formed at the core-shell interface during repeated electrochemical reactions, which deteriorates the performance of the material. Summary of the invention

[0004] The purpose of the present invention is to solve the shortcomings of the prior art and provide a core-shell structure high nickel lithium battery positive electrode material with high capacity and long cycle life, which can improve the ion permeability of the coating layer. The specific scheme is as follows: A method for preparing a high-capacity core-shell structure ultra-high nickel positive electrode material, comprising the steps of: S1) One-time mixing: The concentration gradient structure high nickel multi-element precursor Ni x Co y Mn z (OH)2 and lithium hydroxide powder, and a compound A containing one or more elements of Al, Mg, Zr, Ti, W, V, Mo, B, and Y are uniformly mixed.

[0005] The mixing ratio of high-nickel multi-element precursor NixCoyMnz(OH)2 and lithium hydroxide powder is 1.0:1.02~1.08 in molar ratio, and the addition ratio of compounds containing one or more elements of Al, Mg, Zr, Ti, W, V, Mo, B, and Y is 0.1%~0.5%.

[0006] S2) Primary sintering: A multi-stage sintering process is used, and high-purity oxygen is used for kiln sintering to synthesize LiNi at high temperature by mixing NixCoyMnz(OH)2, lithium hydroxide powder and compound A described in step S1).x Mn y CozM m O2 powder; The primary sintering process adopts a multi-stage sintering process. First, the sintering temperature of each temperature zone is set according to the sintering process requirements, and then the corundum crucible is loaded and placed on the push plate of the tunnel kiln. The sintering is completed at the same time as the push plate moves forward; Among them, the low-temperature sintering stage is heated to 450-650℃ at 1-5℃ / min and kept warm for 2-6h; the high-temperature sintering stage: heats to 700-800℃ at 1-5℃ / min, keeps warm for 4-10h, then naturally cools down to below 100℃, stops oxygen introduction, and carries out coarse crushing by rollers.

[0007] S3) Washing: The LiNi obtained in step S2) x Mn y CozM m O2 powder is mixed with pure water, stirred, filtered and dried; the specific washing process uses vertical filter pressing for water washing to reduce the residual alkali on the surface of high-nickel materials. First, the LiNi obtained in step 2) x Mn y CozM m O2 powder is mixed with pure water in a mixing ratio of 1:1.0-1.8. The stirring time is 1-5 minutes and the filter pressing time is 10-30 minutes. The filter cake is dried on a plow. The plow spindle rotation frequency is 10-40HZ, the drying temperature is 150-200°C, and the drying time is 1-4 hours.

[0008] S4) Secondary mixed coating: The dried material in step S3) is uniformly mixed with Al2O3, Nb2O5 and lithium hydroxide in a high-speed mixer; The secondary mixing and coating process is as follows: the dried material powder obtained in step S3) is mixed with Al2O3, Nb2O5 and lithium hydroxide in a high-speed mixer at a mixing ratio of 0.1wt% to 0.5wt% for coating modification. The coating is carried out using a high-speed mixer with a mixing time of 30-60min and a rotation speed of 800 to 1400r / min.

[0009] S5) Secondary sintering: The coated and modified material in step 4) is sintered in a tunnel kiln, high-purity oxygen is used for kiln sintering, the sintering temperature is 600-700° C., and the insulation time is 5-10 hours to obtain a core-shell structure high-nickel positive electrode material.

[0010] The invention also discloses a high-capacity core-shell structure ultra-high nickel positive electrode material prepared by the preparation method.

[0011] The beneficial effects of the present invention are as follows: 1. The button cell prepared by using the core-shell structure high nickel lithium battery positive electrode material of the present invention has an initial discharge specific capacity (2.8-4.3V) of up to 224.8mAh / g, and a capacity retention rate of 90% after 100 cycles at 45°C, which is comparable to the Li(Ni 0.92 Co 0 .07 Mn 0.01 )O2 positive electrode materials have obvious advantages in discharge capacity and cycle performance.

[0012] 2. The preparation method of the present invention adopts coating Al2O3, Nb2O5 and lithium salt to form active LiAlO2 and LiNbO3 coating layers on the surface of the material at high temperature, thereby improving the ion permeability of the coating layer.

[0013] 3. The preparation method of the present invention has simple process, convenient operation, easy to realize industrial production, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The process flow chart of the preparation method of the present invention is as follows: Figure 2 This is a SEM photo of the core-shell structure cathode material obtained in Example 1; Figure 3 It is a comparison chart of the 45°C high temperature cycle performance test of the positive electrode materials of the embodiment of the present invention and the comparative example. DETAILED DESCRIPTION

[0015] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0016] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0017] Comparative Example 1 A non-core-shell structured high-nickel lithium battery positive electrode material was prepared as a comparative example, and the specific steps were as follows: (1) Using precursor Ni 0.92 Co 0.07 Mn 0.01(OH)2, lithium salt, Al2O3 and MgO are mixed evenly with a high mixer, the molar ratio of precursor to lithium salt is 1:1.04, the molar ratio of Al element to total transition metal is 0.01:1, and the molar ratio of Mg element to total transition metal is 0.01:1. The mixed materials are sintered in multiple stages in a tunnel kiln, wherein, the low-temperature stage is sintered at a temperature of 1-5°C / min to 450-650°C and kept warm for 2-6h; high-temperature stage sintering: the temperature is increased to 700-800°C at a temperature of 1-5°C / min, kept warm for 4-10h, then naturally cooled to below 100°C, oxygen introduction is stopped, and coarse crushing is carried out by rollers.

[0018] (2) A vertical filter press is used for a water washing process to reduce the residual alkali on the surface of the high-nickel material. First, the NCM powder obtained in step (1) is mixed with pure water in a mixing ratio of 1:1.0 to 1.8. The stirring time is 1 to 5 minutes and the filter pressing time is 10 to 30 minutes. The obtained filter cake is dried on a plow. The plow spindle rotation frequency is 10 to 40 Hz, the drying temperature is 150 to 200°C, and the drying time is 1 to 4 hours.

[0019] (3) The NCM dried material obtained in step (2) is sintered in a tunnel kiln. High-purity oxygen is used for sintering in the kiln. The sintering temperature is 650° C. and the insulation time is 8 hours. The sintered NCM is sieved to remove iron to obtain a conventional high-nickel positive electrode material.

[0020] Comparative Example 2 A non-core-shell structured high-nickel lithium battery positive electrode material was prepared as a comparative example, and the specific steps were as follows: (1) Using precursor Ni 0.92 Co 0 .07 Mn 0 .01 (OH)2, lithium salt, Al2O3 and MgO are mixed evenly with a high mixer, the molar ratio of precursor to lithium salt is 1:1.04, the molar ratio of Al element to total transition metal is 0.01:1, and the molar ratio of Mg element to total transition metal is 0.01:1. The mixed materials are sintered in multiple stages in a tunnel kiln, wherein, the low-temperature stage is sintered at a temperature of 1-5°C / min to 450-650°C and kept warm for 2-6h; the high-temperature stage is sintered at a temperature of 1-5°C / min to 700-800°C, kept warm for 4-10h, then naturally cooled to below 100°C, oxygen introduction is stopped, and coarse crushing is carried out by rollers.

[0021] (2) A vertical filter press is used for a water washing process to reduce the residual alkali on the surface of the high-nickel material. First, the NCM powder obtained in step (1) is mixed with pure water in a mixing ratio of 1:1.0 to 1.8. The stirring time is 1 to 5 minutes and the filter pressing time is 10 to 30 minutes. The obtained filter cake is dried on a plow. The plow spindle rotation frequency is 10 to 40 Hz, the drying temperature is 150 to 200°C, and the drying time is 1 to 4 hours.

[0022] (3) The dried NCM obtained in step (2) is mixed evenly with 0.1wt% Al2O3, 0.05wt% Nb2O5 and 0.073wt% lithium hydroxide in a high-speed mixer for 50 min at a speed of 1000 r / min. The mixture is sintered in a tunnel kiln using high-purity oxygen at a sintering temperature of 650°C for 8 h. The sintered NCM is sieved to remove iron to obtain a conventional high-nickel positive electrode material.

[0023] Example (1) Using core-shell structure precursor Ni 0.92 Co 0.07 Mn 0.01 (OH)2, lithium salt, Al2O3 and MgO are evenly mixed in a high mixer, the molar ratio of precursor to lithium salt is 1:1.04, the molar ratio of Al element to total transition metal is 0.01:1, and the molar ratio of Mg element to total transition metal is 0.01:1. The mixed materials are sintered in multiple stages in a tunnel kiln, wherein, the low-temperature stage is sintered at a temperature of 1-5°C / min to 450-650°C and kept warm for 2-6h; high-temperature stage sintering: the temperature is increased to 700-800°C at a temperature of 1-5°C / min, kept warm for 4-10h, then naturally cooled to below 100°C, oxygen introduction is stopped, and coarse crushing is carried out by rollers.

[0024] (2) A vertical filter press is used for a water washing process to reduce the residual alkali on the surface of the high-nickel material. First, the NCM powder obtained in step (1) is mixed with pure water in a mixing ratio of 1:1.0 to 1.8. The stirring time is 1 to 5 minutes and the filter pressing time is 10 to 30 minutes. The obtained filter cake is dried on a plow. The plow spindle rotation frequency is 10 to 40 Hz, the drying temperature is 150 to 200°C, and the drying time is 1 to 4 hours.

[0025] (3) The dried NCM obtained in step (2) is mixed evenly with 0.1wt% Al2O3, 0.05wt% Nb2O5 and 0.073wt% lithium hydroxide in a high-speed mixer for 50 min at a speed of 1000 r / min. The obtained mixture is sintered in a tunnel kiln. High-purity oxygen is used for sintering in the kiln. The sintering temperature is 650°C and the insulation time is 8h. The sintered NCM is sieved to remove iron to obtain the core-shell structure high-nickel positive electrode material. Its SEM scanning photo is as shown in FIG. Figure 2 shown.

[0026] Table 1 Comparison of physical and chemical properties of examples and comparative examples

[0027] Table 1 is a comparison of the physical and chemical properties of the embodiment and the comparative example. It can be seen from Table 1 that the capacity of the comparative example 2 is similar to that of the comparative example 1. This is because Al2O3 and Nb2O5 are coated and added. At high temperature, the active LiAlO2 and LiNbO3 coating layers are formed on the surface of the material by reacting with lithium, which have high ion permeability. There is almost no capacity loss after coating, and from Figure 3 It can be seen that the cycle energy is significantly improved after coating.

[0028] By comparing the embodiment and comparative example 2, it can be seen that compared with the conventional 92 precursor, the core-shell structure 92 precursor has a higher initial discharge capacity. Figure 3 It can be seen that the core-shell structure precursor has better cycling performance. After the three groups of samples are prepared into full electricity, the core-shell structure high-nickel material can stably cycle 1,100 times while the capacity can be maintained at 80%, and there is no obvious powdering of the positive electrode.

[0029] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a high-capacity core-shell structure ultra-high nickel positive electrode material, characterized in that: Includes steps: S1) One-time mixing: The concentration gradient structure high nickel multi-element precursor Ni x Co y Mn z (OH)2 and lithium hydroxide powder, and a compound A containing one or more elements of Al, Mg, Zr, Ti, W, V, Mo, B, and Y are uniformly mixed; S2) Primary sintering: A multi-stage sintering process is used, and high-purity oxygen is used for kiln sintering to synthesize LiNi at high temperature by mixing NixCoyMnz(OH)2, lithium hydroxide powder and compound A described in step 1). x Mn y CozM m O2 powder; S3) Washing: The LiNi obtained in step S2) x Mn y CozM m O2 powder is mixed with pure water, stirred, filtered and then dried; S4) Secondary mixed coating: The dried material in step S3) is uniformly mixed with Al2O3, Nb2O5 and lithium hydroxide in a high-speed mixer; S5) Secondary sintering: The coated and modified material in step S4) is sintered in a tunnel kiln, high-purity oxygen is used for sintering in the kiln, the sintering temperature is 600-700° C., and the insulation time is 5-10 hours to obtain a core-shell structure high-nickel positive electrode material.

2. The method for preparing a high-capacity core-shell structure ultra-high nickel positive electrode material according to claim 1, characterized in that: In the step S1), the mixing ratio of the high nickel multi-element precursor NixCoyMnz(OH)2 and lithium hydroxide powder is 1.0:1.02-1.08 in molar ratio, and the compound containing one or more elements of Al, Mg, Zr, Ti, W, V, Mo, B, and Y is added in an amount of 0.1%-0.5%.

3. The method for preparing a high-capacity core-shell structure ultra-high nickel positive electrode material according to claim 1, characterized in that: The primary sintering process in step S2) adopts a multi-stage sintering process. First, the sintering temperature of each temperature zone is set according to the sintering process requirements. Then, a corundum crucible is loaded and placed on the push plate of the tunnel kiln. The sintering is completed simultaneously with the push plate moving forward. Among them, the low-temperature sintering stage is heated to 450-650℃ at 1-5℃ / min and kept warm for 2-6h; the high-temperature sintering stage: heats to 700-800℃ at 1-5℃ / min, keeps warm for 4-10h, then naturally cools down to below 100℃, stops oxygen introduction, and carries out coarse crushing by rollers.

4. The method for preparing a high-capacity core-shell structure ultra-high nickel positive electrode material according to claim 1, characterized in that: The washing process in step S3) uses a vertical filter press to wash the high-nickel material to reduce the residual alkali on the surface of the high-nickel material. First, the LiNi x Mn y CozM m O2 powder is mixed with pure water in a mixing ratio of 1:1.0-1.

8. The stirring time is 1-5 minutes and the filter pressing time is 10-30 minutes. The filter cake is dried on a plow. The plow spindle rotation frequency is 10-40HZ, the drying temperature is 150-200°C, and the drying time is 1-4 hours.

5. The method for preparing a high-capacity core-shell structure ultra-high nickel positive electrode material according to claim 1, characterized in that: The secondary mixing and coating process of step S4) is as follows: the dried material powder obtained in step 3) is mixed with Al2O3, Nb2O5 and lithium hydroxide in a high-speed mixer at a mixing ratio of 0.1wt% to 0.5wt%, and the coating modification is performed. The coating is performed using a high-speed mixer with a mixing time of 30-60min and a rotation speed of 800 to 1400r / min.

6. A high-capacity core-shell structure ultra-high nickel positive electrode material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 5.